2022
DOI: 10.1161/strokeaha.121.037491
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Mobile Stroke Unit Care in Norway

Abstract: BACKGROUND: Acute ischemic stroke treatment in mobile stroke units (MSUs) reduces time-to-treatment and increases thrombolytic rates, but implementation requires substantial investments. We wanted to explore the cost-effectiveness of MSU care incorporating novel efficacy data from the Norwegian MSU study, Treat-NASPP (the Norwegian Acute Stroke Prehospital Project). METHODS: We developed a Markov model linking improvements in time-to-treatment and throm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 35 publications
1
13
0
1
Order By: Relevance
“…En nylig helseøkonomisk analyse i samarbeid med Folkehelseinstitu et viser at slagambulansebehandling er potensielt kostnadseffektivt i områder der minst 125-260 pasienter kan behandles per slagambulanse per år (12). De e kan vaere realistisk flere steder i Norge (13), og rendezvous-metoden (møtekjøring med vanlig ambulanse) gjør at opptaksområdene kan utvides.…”
Section: Studieresultatene Indikerte Også At Flere Pasienter Med Stor...unclassified
“…En nylig helseøkonomisk analyse i samarbeid med Folkehelseinstitu et viser at slagambulansebehandling er potensielt kostnadseffektivt i områder der minst 125-260 pasienter kan behandles per slagambulanse per år (12). De e kan vaere realistisk flere steder i Norge (13), og rendezvous-metoden (møtekjøring med vanlig ambulanse) gjør at opptaksområdene kan utvides.…”
Section: Studieresultatene Indikerte Også At Flere Pasienter Med Stor...unclassified
“…Economic evaluations of the Melbourne MSU and other MSUs internationally have been previously reported. Three German, [23][24][25] Norwagian 26 and one US 27 study suggested that high costs can be averted in stroke acute care, but the cost-effectiveness was subject to the effectiveness of MSU, staff size, population density, etc. The incremental cost-effectiveness ratio of the Melbourne MSU, which the TASTE-a trial was based on, was very favourable at $30,982 per disability-adjusted life year avoided, falling below the often used willingness to pay per DALY threshold in Australia of AUD 50,000.…”
Section: Discussionmentioning
confidence: 99%
“…Available cost-effectiveness studies from several countries have suggested that MSUs are generally cost-effective. [13][14][15][16] However, the conclusions of these analyses are heavily dictated by starting assumptions. The calculation of incremental cost-effectiveness ratios comparing MSUs with routine EMS care are affected by a large number of factors, which can vary widely between countries, regions, and systems (these include, eg, the organization of existing routine EMS services, costs of alternative MSU staffing models, size of the geographic region assessed, population density, underlying stroke incidence, and number of stroke patients treated by MSU).…”
Section: See Related Article P 415mentioning
confidence: 99%